PERANAN TOUR PLANNER TERHADAP KEDATANGAN WISATAWAN KE DAYA TARIK WISATA KOTA YOGYAKARTA - , KENSRIE DIAH AYUNINGTYAS ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The tourist attraction diversity in Yogyakarta City divided by several thing that is the culture tourist attraction, the museum tourist attraction, education tourist attraction, tour village and annual events. Existence of tour planners in Yogyakarta City can support tourist arrival to Yogyakarta City, Geographically the city of Yogyakarta lies at the centre in the region of Daerah Istimewa Yogyakarta that is why one of point factor tour planners to put up tour package besides the located, the entrance fee, attractionally, and famously the tourist attraction is. Compiler interested the examination and study a role tour planner to arrivaling tourist to the power attraction in Yogyakarta City for knowing the role tour planning can did that. The examination done by the centre of gravity for aspect tourist attraction and role tour planner. Less of tour planner that still exist in Yogyakarta City are not participate in a tour, from the research in 33 travel agent that managed the tour. Author put in 3 samples of 33 travel agent that managed are tour. From that samples, there are some characteristics in the tour package that offered to the tourists. Data collection was done by making direct observation in the field and interviews with stokeholders. The focus do at technique aspect and tourist operational. Technique aspect and operational which means role tour planners to put up the tour package with tourist attraction Yogyakarta City inside it, and saw every tourist attraction via some factor that is located, entrance fee, attraction,famously and tour planner roled up to promoted the objects.